Investigating Environmental Governance's Impact on Financial Performance; Role of Company Size in Indonesian Palm Oil Firms - Bella, Safrina; Setiawan, Hendra (Analisis Data Innovation, 2024)
Objective: This empirical study explores the relationships among environmental governance factors environmental costs, disclosure, performance, firm size, leverage, and financial performance in Indonesian palm oil firms listed on the Indonesia Stock Exchange (IDX) from 2020 to 2023. Methods: Utilizing secondary data from publicly available sources, the study integrates financial metrics (profitability, return on assets, return on equity) and environmental indicators (costs, disclosure, performance). Regression analysis is employed to statistically analyze these relationships.Findings: Findings reveal that environmental costs significantly enhance financial performance, emphasizing the strategic advantage of investing in sustainable technologies and processes. Environmental disclosure also positively impacts financial performance by bolstering investor confidence and consumer trust. Surprisingly, environmental performance does not directly influence financial outcomes, indicating the influence of external factors and industry contexts. Firm size mediates the positive effects of environmental disclosure on financial performance, highlighting larger firms' capabilities in implementing sustainable practices. Moreover, leverage plays a significant role in boosting financial flexibility, contributing to growth and profitability.Novelty: This study contributes to the understanding of the strategic value of environmental governance in the palm oil industry, particularly in the context of emerging markets. It also highlights the unique role of firm size in enhancing the financial benefits of environmental initiatives.Implications: This study underscores the pivotal role of proactive environmental management in driving competitive advantage and sustainable growth for palm oil companies. It advocates for integrating environmental strategies into business models and governance frameworks to achieve long-term financial success.